NITROGEN FERTILIZATION IN IMPLEMENTATION OF Urochloa Brizantha cv. Xaraés IN BRAZILIAN SAVANNA: Nutritional characteristics - Part 2 - Santini, J. M. K.; Perin, A.; Coaguila, D. N.; Valderrama, M.; Galindo, F.S.; dos Santos, C. G.; Silva, V. M.; Buzetti, S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Among the productivity-enhancing factors, fertilization has provided great advances in productivity and quality of pastures, and the nitrogen (N) is emphasized for its large extraction and increasing the productivity of grasses, however, it is influenced by the environment and can be lost if mismanagemented. To minimize this problem, an alternative that has been identified as promising is the use of enhanced efficiency fertilizers. Thus, the aim of the work was to evaluate the effect of sources and doses of N in the implementation of Urochloa brizantha cv. Xaraés (xaraés-grass), in cultivation in the Cerrado conditions. The experiment was conducted at the experimental area in Rio Verde - GO, Brazil, the experimental design was a randomized block with four replications, in a factorial scheme of 3x4. With three sources of N (conventional urea, enhanced efficiency urea and ammonium nitrate); and four N doses (0, 20, 40 and 80 kg N ha-1 clip-1). The use of conventional urea was best alternative for growing xaraés-grass, the enhanced urea was not deemed greater efficiency. The recommended dose of nitrogen is 80 kg ha-1 by clipping, considering the nutritional improvement of dry matter shoot.